To pack or not to pack- A Randomized Clinical Trial comparing the Immediate Outcomes of Packed and Non Packed abscess wounds - Rijal, Bhuhan; Shrestha, Vijay Kumar; Basnet, Robin Bahadur; Pokhrel, Gyan (Journal of Society of Surgeons of Nepal, 2017)
Introduction: The objective of this study was to determine if there was any benefit from routine abscess packing after incision and drainage as compared to incision and drainage alone, as there seems to be emerging literature negating this practice.Methods: A prospective randomized study incorporating abscess from different locations of the body, measuring less than 7 cm, were taken. Incision and drainage was carried out under local or general anesthesia after routine preparation by the surgical resident under guidance of the surgical registrar. The subjects were then randomized into abscess cavity packing and non-packing groups with prescription for antibiotics, analgesics and narcotic analgesics. The subjects were followed up in surgical outpatient by the same resident, where the wound was examined, pain was noted for the duration using the VAS and number of narcotic analgesics taken were noted.Results: Total of 92 patients was included divided equally in both groups. There was equality within the two groups regarding age, sex and location of abscess. The primary outcome, which was to find out the need for intervention in the first 48 hours after the procedure was compared and there was no significant difference in the interventions needed in the first 48 hours between the two groups (p= 0.49, difference in means =.536, 95% CI = -2.14 to 1.07). There was no difference in the overall pain perceived by the patients of the two groups, as the total patients who experienced pain were 77, of which 41(53.2%) were in the wound packed group and 36 (46.8%) non-packed group, (difference in means = 0.783, 95% CI= 0.40 to 1.16, p=0.75), but of the 19 patients who experienced severe pain, 15 were from the packed group and 4 were from the non-packed group (p = 0.02). 29 patients from the packed group required narcotic analgesics whereas only 12 from the non-packed group required them (p=0.009, 95% CI= 0.20 to 0.58).Conclusion: Packing of the abscess cavity does not carry any added benefit as compared to Incision and Drainage alone and it causes more severe pain and discomfort to the patient with increased analgesic requirements.